PERANCANGAN DAN STUDI KELAYAKAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) ROOFTOP PADA HOTEL GRAND DAFAM YOGYAKARTA - Mohammad Fathurrahman Surya Pratama; Moch. Dhofir; Lunde Ardhenta (Jurnal Mahasiswa TEUB, 2023)
This research discusses about the design of an on-grid PLTS system on the rooftop of Hotel Grand Dafam Yogyakarta. For designing PLTS design, researchers used a simulation software called HelioScope, based on design, 140 monocrystalline panels placed with optimal azimuth angle of 25,78o and a tilt of 10o , 2 inverter with a capacity 50kW, 1 smart meter, and other support components of PLTS system. From the economic analysis is gained for initial investment required for this PLTS system is Rp965.859.193,64 with operational and maintenance cost on each year is Rp14.487.887,90, and Cost of Energy (COE) isRp0.858/kWh. The result for feasibilty analysis of rooftop PLTS for Net Present Value (NPV) is Rp4.305.724.376,35 with Internal Rate of Return 17,46% and BCR rate 5,457, Because these three aspects are positive, it can be concluded that this PLTS system investment is feasible to realized. Keywords : PLTS Rooftop, On – Grid System, HelioScope, Feasibility Analysis